Continuity and Discontinuity in Basic Education Learning: Causality Isolation Policy in Avoiding the Spread of COVID-19 - Nahdi, Khirjan; Ramdhani, Sandy; Lutfi, Samsul; Marzuki, Muhammad; Asror, M Zainul (Universitas Islam Negeri Raden Intan Lampung, 2020)
The COVID-19 outbreak is a non-natural disaster and has an impact on learning continuity. This study aimed to find the reality of the continuity/discontinuity of learning of primary education students in East Lombok during student isolation in the prevention of COVID-19. Data obtained through surveys and interviews with 198 respondents representing school principals, teachers, students, parents, and the community. According to the Bayesian Approach to Learning Causal Networks, the data were analyzed descriptively through frequency distribution and causal analysis. It was found that 57.07 % of respondents claimed they did not know the purpose of the isolation policy, so it was not explained. Exactly 54.76 % of respondents admitted to isolation as a holiday, 54 % of respondents admitted to playing to their heart's content during the isolation period, 88.77 % of respondents admitted that this policy was not coordinated, and 100 % of respondents admitted that they did not maximize the function of online learning. The contextual condition of this isolation period is a causal event between a lack of understanding of the policy intent or P (A), causing unclear instructions, or P (B). Unclear teacher instruction or P (B) causes students not to study at home during isolation, or learning discontinuity occurs, with code P (C). Lack of understanding of the intent of the isolation policy, or P (A) causes this policy not to be coordinated with interested parties. Due to unclear instructions, the utilization of online learning, or P (E) is not optimal. The study results are urgent and have implications for the policy of learning from home as well as the coordination pattern of educational stakeholders in the COVID-19 phase.